Working situation of cancer survivors versus the general population. - Lee, Myung Kyung; Yun, Young Ho (Journal of Cancer Survivorship, 2015)
Purpose: The purposes of this study were to compare the working situation of cancer survivors and the general (cancer-free) population and investigate characteristics associated with the increased likelihood of unemployment between the two groups.Methods: We selected 1927 cancer survivors from the 2008 Korean Community Health Survey data less than 65 years of age and used propensity score matching to randomly select 1924 individuals from the general population who closely resembled the cancer survivors.Results: Compared to the general population, cancer survivors were less likely to be engaged in paid work, particularly as permanent workers, and were more likely to work regular hours. Additionally, they tended to do less work that involved lifting or moving heavy objects and uncomfortable postures and were more willing to express their emotions. An increased probability of unemployment among cancer survivors was associated with being over 50 years old, being female, having a lower monthly income, having multiple comorbidities, belonging to a nuclear family, being a National Basic Livelihood Act beneficiary, and having a recent diagnosis.Conclusion: Cancer survivors may want to pursue flexible occupations and improve their working situation. Further, they perceive their workplace more positively compared to the general population.Implications For Cancer Survivors: Respecting the cancer survivor's choice to find flexible working conditions that suit their health needs and status, health-care providers involved in managing work-related issues among cancer survivors should be aware of the interaction between work-related concerns and post-cancer disease management.